Горизонтальне вирівнювання обласних бюджетів України в умовах децентралізації - Бойко, Світлана Василівна; Гошовська, Валентина Василівна; Гнатенко, Олена Андріївна (My University, 2019)
У статті проведено дослідження міжрегіональних диспропорцій горизонтального вирівнювання обласних бюджетів та оцінено їх стан в умовах децентралізації. Розкрито особливості горизонтального вирівнювання обласних бюджетів України за допомогою дотації вирівнювання у 2011-2014 роках та базової або реверсної дотації у 2015-2017 роках. Проаналізовано звітні дані Державної казначейської служби України про розміри горизонтального вирівнювання обласних бюджетів, застосовано технологію кластерного аналізу методом Варда (Уорда) з нормалізованими значеннями евклідових відстаней та сформовано п’ять кластерів. Проведено порівняння результатів кластерного аналізу у дореформений період та період реалізації реформи децентралізації, зроблено висновки про відсутність тісного зв’язку між міжрегіональною диференціацією горизонтального вирівнювання обласних бюджетів України. Найбільші зміни характерні для обласного бюджету Донецької та Чернівецької областей. До обласних бюджетів, які перемістилися до кластерів з меншим розміром базових дотацій належать обласні бюджети Луганської, Вінницької, Одеської областей. До обласних бюджетів, які перемістилися до кластерів з більшим розміром базових дотацій належать обласні бюджети Закарпатської, Волинської, Кіровоградської, Рівненської, Сумської, Тернопільської та Чернігівської областей. Excessive centralization of budget funds in the State Budget of Ukraine, the insufficiency of the revenue base of local budgets has led to the need for horizontal and vertical equalization technologies that require increased attention in the current conditions for the establishment of decentralization of power and the creation of financial basis for the activities of local governments. Purpose. The purpose of the study is to prove or refute the hypothesis of the existence and modification of interregional disproportions of the horizontal equalization of local (region) budgets and the analysis of their state in conditions of decentralization. Results. The specifics of the horizontal equalization of the region budgets of Ukraine with application of the equalization subsidies in 2011-2014 and the basic or reverse subsidies in 2015-2017 are discovered. Reporting data of the State Treasury of Ukraine on the size of horizontal equalization of region budgets are analyzed. The technology of cluster analysis by the Ward’s method with squared Euclidean distances are applied and five clusters are formed. Results of cluster analysis in 2011-2014 and 2015-2017 are compared and made conclusions about the lack of correlation between the interregional differentiation of horizontal equalization of region budgets of Ukraine. The biggest changes are characteristic for the region budget of Donetsk and Chernivtsi regions. Oblast budgets, that moved to clusters with less basic subsidies include region budgets of Luhansk, Vinnitsa, Odesa regions. The oblast budgets, that have moved to clusters with larger of basic subsidies include region budgets of Zakarpattia, Volyn, Kirovograd, Rivne, Sumy, Ternopil and Chernihiv regions. Conclusions. According to the results of the study, the existence of interregional disproportions of horizontal equalization of region budgets of Ukraine and their strengthening in conditions of decentralization are proved. The basic subsidies from the State Budget of Ukraine received 18 region budgets in 2015-2016 and 17 region budgets in 2017 against the equalization subsidies of all region budgets in 2011-2014. Financial independence was characteristic of region budgets of Dnipropetrovsk, Donetsk, Zaporizhzhia, Kyiv, Odesa, Poltava and Kharkiv regions.
Keywords: обласні бюджети; кластерний аналіз; дотація вирівнювання; горизонтальне вирівнювання; реверсна дотація; базова дотація; бюджетна децентралізація; cluster analysis; region budgets; budget decentralization; basic subsidies; reverse subsidies; equalization subsidies; horizontal equalization; кафедра фінансів